2016
DOI: 10.1016/j.combustflame.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

PAH formation in counterflow non-premixed flames of butane and butanol isomers

Abstract: Butane and butanol isomers Polycyclic aromatic hydrocarbon (PAH) Soot formation PAH-planar laser-induced fluorescence (PAH-PLIF) Laser-Induced incandescence (LII) Light extinction a b s t r a c t Using the planar laser-induced fluorescence (PLIF) technique in a counterflow non-premixed flame configuration, the formation of the polycyclic aromatic hydrocarbons (PAHs) for the butane isomers and the butanol isomers was investigated. For these C 4 fuels, the PAHs of various aromatic ring size groups (2, 3, 4, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…The interference from soot particles, due to resonant radiation from laser induced incandescence, on PAH LIF measurement in diffusion flames is well-known [21,29,37,38]. A simple soot isolation technique, described in [39], was used to measure the amount of soot present in the flames; no interference from soot was observed at the flow conditions used in this study in the region of interest (ROI).…”
Section: Simultaneous Oh and Pah Lif Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…The interference from soot particles, due to resonant radiation from laser induced incandescence, on PAH LIF measurement in diffusion flames is well-known [21,29,37,38]. A simple soot isolation technique, described in [39], was used to measure the amount of soot present in the flames; no interference from soot was observed at the flow conditions used in this study in the region of interest (ROI).…”
Section: Simultaneous Oh and Pah Lif Imagingmentioning
confidence: 99%
“…which was fitted with a UV 100 mm f/2.8 Cerco lens and a combination of UG11 and WG305 Schott glass filters. of excitation wavelengths from UV to visible [13,42] with the corresponding emission wavelength dependent on the number of aromatic rings possessed by the PAH molecule, and increasing with the number of aromatic rings [11,21,43]. Vander Wal et al [44] reported that with excitation wavelength below 300 nm, PAH with 2 or 3 aromatic rings can fluoresce between 300-350 nm while PAHs of 4 rings or more can exhibit fluorescence in the range 300-700 nm.…”
Section: Simultaneous Oh and Pah Lif Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the fundamental combustion system of the butanol. [109][110][111][112][113][114] Author Singh et al 110,111 n/iso/sec/tert-Butanol and the gasoline-diesel flame may not occur as synergistic as in the methane laminar diffusion flame. Liu et al 114 studied the effect of n-butanol addition on the formation of soot in a gasoline laminar diffusion flame by TC-LII technology and constructed a semi-detailed mechanism of n-butanol-TRF-PAHs for chemical kinetics analysis.…”
Section: Research On Butanol In Fundamental Combustion Systemmentioning
confidence: 99%
“…However, the results are different in different combustion modes. Singh and colleagues 110,111 found that the butane isomer produced more soot than the butanol isomer in the atmospheric non-premixed counterflow flame due to the action of the OH group. They also pointed out that in addition to C 3 H 3 , C 2 H 2 also plays an important role in the formation and growth of PAHs.…”
Section: Butanolmentioning
confidence: 99%